The Effects of Financial Aid Loss on Persistence and Graduation: A Multi-Dimensional Regression Discontinuity Approach - Todd R. Jones; Daniel Kreisman; Ross Rubenstein; Cynthia Searcy; Rachana Bhatt (Institute of Labor Economics (IZA), 2020)
For years Georgia's HOPE Scholarship program provided full tuition scholarships to high achieving students. State budgetary shortfalls reduced its generosity in 2011. Under the new rules, only students meeting more rigorous merit-based criteria would retain the original scholarship covering full tuition, now called Zell Miller, with other students seeing aid reductions of approximately 15 percent. We exploit the fact that two of the criteria were high school GPA and SAT/ACT score, which students could not manipulate when the change took place. We compare already-enrolled students just above and below these cutoffs, making use of advances in multi-dimensional regression discontinuity, to estimate effects of partial aid loss. We show that, after the changes, aid flowed disproportionately to wealthier students, and find no evidence that the financial aid reduction affected persistence or graduation for these students. The results suggest that high-achieving students, particularly those already in college, may be less price sensitive than their peers.
Keywords: I22; I23; H75; 330; student aid; multi-dimensional regression discontinuity; HOPE